2022
DOI: 10.1093/ndt/gfac053
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 treatment preserves antioxidant status and attenuates renal fibrosis in rats with unilateral ureteral obstruction

Abstract: Background Nesfatin-1 (NES-1), an anorexigenic peptide, was reported to have anti-inflammatory and anti-apoptotic actions in several inflammation models. Methods To elucidate potential renoprotective effects of NES-1, unilateral ureteral obstruction (UUO) was induced in male Sprague Dawley rats by ligating left ureters. The rats were injected intraperitoneally with either saline (SL) or NES-1 (10 μg/kg/day) for 7 or 14 days (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recent studies have demonstrated the antioxidant properties of Nesfatin-1, highlighting its involvement in the development and progression of various diseases [29]. For instance, Nesfatin-1 has been shown to preserve antioxidant status and attenuate renal fibrosis in rats with unilateral ureteral obstruction [30]. Additionally, treatment with Nesfatin-1 has been found to alleviate cerebral ischemia-reperfusion injury by inhibiting neuronal cell death and enhancing antioxidant defenses [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the antioxidant properties of Nesfatin-1, highlighting its involvement in the development and progression of various diseases [29]. For instance, Nesfatin-1 has been shown to preserve antioxidant status and attenuate renal fibrosis in rats with unilateral ureteral obstruction [30]. Additionally, treatment with Nesfatin-1 has been found to alleviate cerebral ischemia-reperfusion injury by inhibiting neuronal cell death and enhancing antioxidant defenses [31].…”
Section: Discussionmentioning
confidence: 99%
“…It also suppresses free radical formation. [27,38] On the other hand, Nesfatin-1 inhibits inflammation by modulation of various inflammation-related signaling pathways, including the NF-κB pathway, Akt/GSK-3β pathway, and CREB signaling pathway. This leads to a decrease in the subsequent release of inflammatory mediators such as IL-1β and TNF-α.…”
Section: Nesfatin-1 Suppressed Hyperoxia-induced Os In Aeciismentioning
confidence: 99%
“…Dapagliflozin attenuated renal fibrosis by inhibiting RIP1-RIP3-MLKL signaling pathway-mediated necroinflammation in unilateral ureteral obstruction [ 79 ]. Nesfatin-1 (NES-1) ameliorated UUO-induced renal fibrosis, which may be associated with the inhibition of neutrophil infiltration, thereby ameliorating oxidative stress and inflammation [ 80 ]. Dual soluble epoxide hydrolase inhibitor-PPAR-γ agonist (RB394) alleviated renal fibrosis by reducing renal inflammation, oxidative stress, tubular injury and vascular injury [ 81 ].…”
Section: Treatment Of Renal Interstitial Fibrosis In Obstructive Neph...mentioning
confidence: 99%